The prevalence of iodine deficiency disorders among schooldren in public elementary schools in the municipality of Virac, Catanduanes - Gianan, Elena V.; de la Paz, Margarita (1995)
The study determined the prevalence of iodine deficiency disorders (IDD) and some o fits etiological factor such as environmental goitrogens, dietary intake of iodine, physiologic factors (age and sex), and nutritional status. Schoolchildren aged 6 years to 14 years old and above residing in coastal, plains and mountainous areas, selected by means of stratified cluster random sampling were the subjects of the study. A total of 2, 486 schoolchildren were covered in the clinical assessment phase by physical examination, which included palpitation method for detection of goiter. A subsample of 299 children were included in the dietary and biochemical assessment including determination of urinary iodine excretion (UIE) and thyroid stimulating hormone (TSH) level and nutrient intake of the subjects. Using the palpitation method, the overall prevalence rate of goiter was 2.1%, with the highest percentage found in plain areas. No gross hypothyroidism and hyperthyroidism were found in the area. Prevalence of goiter was higher in females than in males (4:1). There was no difference in the goiter prevalence rate (GPR) among the different age groups. Clinical vitamin A deficiency was associated with goiter was not found in the population studied. Urinary iodine excretion (UIE), indicated mild to moderate iodine deficiency among the subjects. It was found that 8.4% of the subjects had a TSH level greater than 5.0 uIU/ml, indicating increased demands for thyroid hormone production with the highest percentage in the plains. In the correlation analysis, TSH levels were negatively correlated with age and weight-for-age. No significant relationship between TSH level and the other etiological factors such as ht-for-age, wt-for-ht, Vitamin A, Protein, Iodine and Energy Intake. Results of the dietary data showed deficiencies in energy, protein, vitamin A and iodine intakes. The mean daily iodine intake of the subjects was 37 ug., 41 ug., and 37 ug. in coastal, plains and mountainous areas, respectively. Vitamin A intake was adequate for the subjects from the mountainous areas but inadequate in the plains and coastal areas. Goitrogenic foods which were seldom eaten, were insignificant, since all the food items (kamote, kamoteng kahoy, labanos, labong, etc.) were eaten in cooked form, except singkamas. A relationship between the source of water (positive for E. coli) and urinary iodine excretion (UIE) level was analyzed using the chi-square test. It was found that there was a significant relationship between these two variables. This may indicate that the giotrogenic affect of E. coli found in water may play a role in the IDD problem. Iodine deficiency disorder was present in the area as shown by low levels of urinary iodine excretion, elevated TSH levels, and dietary iodine inadequacy. Since iodine deficiency is definitely present in the area studied, proper intervention to prevent iodine deficiency should be taken up in the community especially among the vulnerable groups (child-bearing women, preschoolers, schoolchildren and other members of the community). A similar study should also be conducted in other towns of the province to determine the magnitude of IDD problem and further investigation of the different etiologies of IDD should be carried out so that appropriate intervention program can be undertaken. Moreover, an intensive information campaign, education and communication about IDD, its consequences and ease of its correction should be undertaken in the community by the different line agencies spear headed by the Department of Health.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Iodine deficiency diseases -- Philippines -- Virac; Goiter; Nutrition disorders in children -- Philippines -- Virac